Training Novices in Generation and Analysis of High‐Dimensional Human Cell Phospho‐Flow Cytometry Data. Issue 1 (6th April 2020) - Roe, Caroline E.; Hayes, Madeline J.; Barone, Sierra M.; Irish, Jonathan M.
Abstract: This article presents a single experiment designed to introduce a trainee to multiple advanced bench and analysis techniques, including high‐dimensional cytometry, profiling cell signaling networks, functional assays with primary human tissue, and single‐cell analysis with machine learning tools. The trainee is expected to have only minimal laboratory experience and is not required to have any prior training in flow cytometry, immunology, or data science. This article aims to introduce the advanced research areas with a design that is robust enough that novice trainees will succeed, flexible enough to allow some project customization, and fundamental enough that the skills and knowledge gained will provide a template for future experiments. For advanced users, the updated phospho‐flow protocol and the established controls, best practices, and expected outcomes presented here also provide a framework for adapting these tools in new areas with unexplored biology. © 2020 by John Wiley & Sons, Inc. Basic Protocol : Phospho‐protein stimulation and mass cytometry data collection Support Protocol : Analysis of signaling mass cytometry data